The experience of infertility treatment: the male perspective. (1st October 2016) - Arya, Shafali Talisa; Dibb, Bridget
Abstract: Current research surrounding infertility is focused primarily on women alone, thus removing men from the fertility equation. However, alternative research has indicated that, although men also experience infertility, there is a paucity of research on men. Therefore, very little is understood about the experiences of infertility from the male perspective. This study adopted a qualitative approach in an attempt to explore the infertility experience from the perspective of men. Fifteen men who had experienced infertility were interviewed to explore their experiences. Interpretative phenomenological analysis was used to analyse the data. Five superordinate themes were developed, and these included: (1) the influence of society on infertility; (2) feeling unacknowledged; (3) natural verses assisted conception; (4) emotional reactions; and (5) improving the infertility experience. The findings of this research indicated that men experience infertility as a mentally, physically and socially demanding condition. Comparisons to previous research have been made, and future research is proposed.